GST-omega genes interact with environmental tobacco smoke on adult level of lung function - de Jong, Kim (BioMed Central, 2013)
BACKGROUND: Lung growth in utero and lung function loss during adulthood can be affected by exposure to environmental tobacco smoke (ETS). The underlying mechanisms have not been fully elucidated. Both ETS exposure and single nucleotide polymorphisms (SNPs) in Glutathione S-Transferase (GST) Omega genes have been associated with the level of lung function. This study aimed to assess if GSTO SNPs interact with ETS exposure in utero and during adulthood on the level of lung function during adulthood. METHODS: We used cross-sectional data of 8,128 genotyped participants from the LifeLines cohort study. Linear regression models (adjusted for age, sex, height, weight, current smoking, ex-smoking and packyears smoked) were used to analyze the associations between in utero, daily and workplace ETS exposure, GSTO SNPs, the interaction between ETS and GSTOs, and level of lung function (FEV(1), FEV(1)/FVC). Since the interactions between ETS and GSTOs may be modified by active tobacco smoking we additionally assessed associations in never and ever smokers separately. A second sample of 5,308 genotyped LifeLines participants was used to verify our initial findings. RESULTS: Daily and workplace ETS exposure was associated with significantly lower FEV(1) levels. GSTO SNPs (recessive model) interacted with in utero ETS and were associated with higher levels of FEV(1), whereas the interactions with daily and workplace ETS exposure were associated with lower levels of FEV(1), effects being more pronounced in never smokers. The interaction of GSTO2 SNP rs156697 with in utero ETS associated with a higher level of FEV(1) was significantly replicated in the second sample. Overall, the directions of the interactions of in utero and workplace ETS exposure with the SNPs found in the second (verification) sample were in line with the first sample. CONCLUSIONS: GSTO genotypes interact with in utero and adulthood ETS exposure on adult lung function level, but in opposite directions.